(untitled) (Research, Society and Development, 2022)
Currently, the new virus called SARS-CoV-2, which causes the disease COVID-19, has caused a pandemic. Self-medication by the population was influenced by the media, through fake news and debates without scientific basis. The most used antibiotic was azithromycin, which is a drug from the macrolide group. The aim of this article is to describe and evaluate the consequences of the irrational use of the antibiotic Azithromycin during the COVID-19 pandemic. This is a systematic review that was carried out according to the recommendations of the PRISMA method. A bibliographical survey of indexed productions was carried out in the following electronic databases Scientific Electronic Library Online (SCIELO), in PubMed and VHL from January 2020 to June 2022. 10 articles were selected for this systematic review, the articles were analyzed and interpreted, with that, studies reported that most patients who were undergoing treatment for COVID-19 with Azithromycin or association with another drug did not have a significant improvement, in one study a combination of azithromycin with hydroxychloroquine proved to be more efficient for reduce viral load. The irrational use of this drug, in addition to increasing the incidence of adverse drug reactions, can contribute significantly to the increase in microbial resistance, requiring information and health education measures for physicians, other health professionals and users, in order to avoid the use and inappropriate prescription of these drugs.